PENGARUH CURRENT RATIO (CR), DEBT TO EQUITY RATIO (DER), RETURN ON ASSET (ROA) TERHADAP DIVIDEND PAYOUT RATIO (DPR) PADA PERUSAHAAN LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2021 - Paolinus Hulu; Ria Hartati; Rachma Nadhila Sudiyono; Woro Dwi Hartanty; Nur Ramawati; Ipang Sasono (Jurnal Penelitian Multidisiplin Ilmu, 2023)
Every company is always oriented towards the growth and survival of a business. The dividend payout ratio shows the percentage of the company's profit paid to shareholders in cash. Dividend policy relates to determining the amount of Dividend Payout Ratio, namely the percentage of net profit after tax distributed as dividends to shareholders. Dividend decisions are part of the company's spending decisions, especially with regard to the company's internal spending. The size of the dividend distributed will affect the size of the retained earnings. The purpose of this study was to determine the effect of Current Ratio (Cr), Debt To Equity Ratio (Der), Return On Asset (Roa) on Dividend Payout Ratio (Dpr) in Lq45 companies listed on the Indonesia Stock Exchange in 2018-2021. The data collection technique in this study used documentation techniques. Sampling using purposive sampling method using certain criteria. The data was analyzed using the help of SPSS. The first research result shows that Current Ratio, Debt to Equity Ratio and Return on Asset have an effect on Dividend Payout Ratio in LQ45 companies listed on the Indonesia Stock Exchange in 2018-2021. The second shows that Current Ratio and Debt to Equity Ratio have no effect on Dividend Payout Ratio. The third shows that Return on Asset has an influence on the Dividend Payout Ratio in LQ45 companies listed on the Indonesia Stock Exchange in 2018-2021.